Measuring telomere length and telomere dynamics in evolutionary biology and ecology. Issue 4 (2nd March 2014) - Nussey, Daniel H.; Baird, Duncan; Barrett, Emma; Boner, Winnie; Fairlie, Jennifer; Gemmell, Neil; Hartmann, Nils; Horn, Thorsten; Haussmann, Mark; Olsson, Mats; Turbill, Chris; Verhulst, Simon; et al.
Summary Telomeres play a fundamental role in the protection of chromosomal DNA and in the regulation of cellular senescence. Recent work in human epidemiology and evolutionary ecology suggests adult telomere length (TL) may reflect past physiological stress and predict subsequent morbidity and mortality, independent of chronological age. Several different methods have been developed to measure TL, each offering its own technical challenges. The aim of this review is to provide an overview of the advantages and drawbacks of each method for researchers, with a particular focus on issues that are likely to face ecologists and evolutionary biologists collecting samples in the field or in organisms that may never have been studied in this context before. We discuss the key issues to consider and wherever possible try to provide current consensus view regarding best practice with regard to sample collection and storage, DNA extraction and storage, and the five main methods currently available to measure TL. Decisions regarding which tissues to sample, how to store them, how to extract DNA, and which TL measurement method to use cannot be prescribed, and are dependent on the biological question addressed and the constraints imposed by the study system. What is essential for future studies of telomere dynamics in evolution and ecology is that researchers publish full details of their methods and the quality control thresholds they employ.